Manual of Spine Surgery - Vieweg, Uwe.; Grochulla, Frank; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This manual of spine surgery has become necessary as a consequence of the rapid expansion of instrumented spine surgery using different minimally invasive and non-fusion techniques. To do justice to this development, the manual aims to present the different techniques to spinal surgeons (orthopaedic and neurosurgeons) in a clear and instructive way using detailed illustrations. The description of different open, less invasive or minimally invasive techniques will provide the spinal surgeon with useful guidelines for their use. The success of any spinal operation depends on good definition of the indications, consideration of the contraindications, technical and organisational factors, good operating technique and correct preoperative preparation and positioning of the patient. These points are presented in this book as clearly as possible and are illustrated with detailed high quality artwork.
General aspects of spinal surgery -- Anterior upper cervical spine -- Anterior cervical spine C3 to C8 (T1) -- Posterior cervical spine -- Anterior thoracic spine -- Posterior thoracic spine -- Anterior lumbar spine -- Posterior lumbar spine.
Keywords: Medicine; Neurosurgery; Orthopedic surgery; Medicine & Public Health; Surgical Orthopedics; Neurosurgery